Growth and yield of new generation clones of Hevea under the agroclimate of sub-Himalayan West Bengal - Das, G.; Meenakumari, T.; Meti, S.; Kumar, S.; Mydin, Kavitha K. (Journal of Plantation Crops, 2015)
Five rubber (Hevea brasiliensis) clones of the RRII 400 series derived from a cross involving RRII 105 and RRIC 100, along with five other popular clones viz. PB 217, RRII 176, RRII 203, RRII 105 and RRIM 600, were evaluated in Jalpaiguri district of sub- Himalayan West Bengal. Growth of clones in the immature and mature phases, rubber yield over seven years of tapping, biomass and timber yield were recorded for assessing the suitability of clones to the region. Clones RRII 429, RRII 417 and RRII 203 were superior in performance in the region compared to the recommended clone RRIM 600. Estimates of genetic parameters revealed comparatively high heritability and scope for improvement of rubber yield by selection.